Immune Consequences of Chlamydia Infections in Pregnancy and In Vitro Fertilization Outcome - M. Askienazy-Elbhar (Hindawi Limited, 1996)
This review addresses the immune consequences of Chlamydial infections in pregnancy and in vitro fertilization (IVF) outcome. In pregnancy, many works have shown the risk for perterm labor, preterm birth, or miscarriage with current infection, and stress the need for screening and treatment early in pregnancy. IVF outcome needs to be studied in relation to specific markers like inflammatory cytokines and secretory antibodies to the 60 kD heat shock protein (hsp60) and to Chlamydia, to determine their ability to predict and influence pregnancy outcome.